1998
DOI: 10.1111/j.1600-0773.1998.tb01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microtubules in Glucose Uptake by C6 Glioma Cells

Abstract: Abstract:Drugs that influence tubulin function were used to investigate the role of microtubules in hexose uptake by C6 glioma cells. In C6 cells, colchicine and vinblastine (which inhibit tubulin polymerization) inhibited radioactive ['H]2-deoxy-D-glucose uptake by about 30%". Paclitaxel (which promotes tubulin polymerization) stimulated hexose uptake by about 25%. To further demonstrate that microtubules play a role in hexose uptake, C6 cells were transfected with GLUT1 cDNA and then challenged with 100 nM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Second, syntaxin 1C may act on the cytoskeleton. It was demonstrated recently that components of the cytoskeleton, such as microtubules and actin filaments, are necessary for the translocation of GLUT-1 and GLUT-4 to the plasma membrane (32)(33)(34). From this viewpoint, it is interesting that syntaxin 1C possesses a tubulin binding motif in the N-terminal region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, syntaxin 1C may act on the cytoskeleton. It was demonstrated recently that components of the cytoskeleton, such as microtubules and actin filaments, are necessary for the translocation of GLUT-1 and GLUT-4 to the plasma membrane (32)(33)(34). From this viewpoint, it is interesting that syntaxin 1C possesses a tubulin binding motif in the N-terminal region.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA (20 g) isolated from native and transfected (see below) T98G cells was separated by electrophoresis in 1.0% formaldehyde-agarose denaturing gels. The EcoRI-digested 600-bp fragments of the GLUT-1 and GLUT-3 cDNA were labeled with 32 P by random priming. The GLUT-1 and GLUT-3 cDNAs were a kind gift from Dr. Shinya Nagamatsu (Kyorin University, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…These filaments are also involved in the integration of signals transduction related to the determination of cell size and the regulation of cell migration and cell survival (Pallari and Eriksson 2006). Microtubules are involved in glucose uptake and transport, as well as the metabolism of tumor cells that is closely correlated with proliferation and hypermetabolism (Singh et al 1998;Nagamatsu et al 1996). It is necessary to understand the cytoskeletal structure and function of glioma cells to better investigate glioma invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that GLUT translocation to the PM is dependent on the cytoskeletal systems including microtubules (MTs) and actin filaments (Dransfeld et al, 2001;Singh et al, 1998;Tong et al, 2001;Wang et al, 1998). For example, drugs that influence the function of tubulin polymerization, such as vinblastine and paclitaxel, alter glucose uptake activity by GLUT1 in glioma cells (Singh et al, 1998). It has also been reported that the GLUT4 vesicular transport depends on cortical actin remodeling (Dransfeld et al, 2001;Tong et al, 2001;Wang et al, 1998) that is regulated by a direct link between SNARE proteins and the MT network (Pooley et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that GLUT translocation to the PM is dependent on the cytoskeletal systems including microtubules (MTs) and actin filaments (Dransfeld et al, 2001;Singh et al, 1998;Tong et al, 2001;Wang et al, 1998). For example, drugs that influence the function of tubulin polymerization, such as vinblastine and paclitaxel, alter glucose uptake activity by GLUT1 in glioma cells (Singh et al, 1998).…”
Section: Introductionmentioning
confidence: 99%